1980
DOI: 10.1136/gut.21.12.1024
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy in Crohn's disease.

Abstract: Cancer morbidity has been evaluated in a series of 513 patients with Crohn's disease under long-term review between 1944-76. In comparison with morbidity rates for cancer in the West Midlands Region (the geographical area from which these patients were drawn) the 31 tumours that occurred represented a relative risk of 1.7 (p < 001) of cancer at all sites. For tumours at sites within the digestive system the relative risk was 3.3 (p < 000 1). A significant excess of tumours was found in both the upper (P < 0.01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
0
7

Year Published

1983
1983
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(114 citation statements)
references
References 11 publications
3
104
0
7
Order By: Relevance
“…Weedon et al [5] reported colorectal cancer in 8 of 449 patients with Crohn's disease, or about 1.2% (i.e., an estimated 20 times greater risk than a control population). Similarly, Gyde et al [6] described an approximately 4-fold increased risk in patients with Crohn's disease. More recent cohort and population-based studies from Canada, where reporting of malignant disease is legally mandated [7,9] , are also consistent with an increased intestinal cancer risk in Crohn's disease.…”
Section: Crohn's Disease and Cancer Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Weedon et al [5] reported colorectal cancer in 8 of 449 patients with Crohn's disease, or about 1.2% (i.e., an estimated 20 times greater risk than a control population). Similarly, Gyde et al [6] described an approximately 4-fold increased risk in patients with Crohn's disease. More recent cohort and population-based studies from Canada, where reporting of malignant disease is legally mandated [7,9] , are also consistent with an increased intestinal cancer risk in Crohn's disease.…”
Section: Crohn's Disease and Cancer Riskmentioning
confidence: 99%
“…If colorectal cancer does develop, however, the prognosis is recognized to be poor with reduced survival [4] . Several studies, again from tertiary care centers, have suggested that patients with Crohn's disease have an increased risk of colorectal cancer [5,6] and an excess overall mortality attributed to digestive tract tumors, including small bowel carcinoma [7] . The latter occur at a younger age, usually in males compared to those with small bowel carcinoma unrelated to Crohn's disease [8] .…”
Section: Crohn's Disease and Cancer Riskmentioning
confidence: 99%
“…In this cohort, consisting of patients from [42][43][44], in some cases the tumor has been diagnosed in regions of the intestine devoid of endoscopic or pathological signs of inflammation [36,[45][46][47] …”
Section: Incidence and Risk Factors Of Crc In Crohn`s Diseasementioning
confidence: 99%
“…A DC pode ser encontrada em todo o tubo digestivo, sendo que compromete preferencialmente íleo distal e cólon (30 a 55%), intestino delgado, quase sempre em seu segmento distal (25 a 35%) e cólon (15 a 25%) 10,11 . No câncer do intestino delgado, a localização mais comum é o íleo distal (73 a 76%), ao contrá-rio do que acontece na população geral, em que o duodeno e o jejuno são os segmentos mais acometidos 1,5,12,13,14,15 .…”
Section: Discussionunclassified